2006
DOI: 10.1177/875687050602500104
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Cultural Knowledge and Understanding of American Indian Students and Their Families: Impact of Culture on a Child's Learning

Abstract: This manuscript discusses educational practices used in a K-12 reservation school system and speculates how these practices may be culturally insensitive to American Indian students and their families in the community. Focus group discussions were conducted with seven teachers, who were students in a graduate program, and were working on a reservation school located in a rural community in the southwestern United States. The students were queried as a group during class meetings on educational practices. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…A primary reason for less participation is that rural parents have to travel considerably further distances to par ticipate in the special education process. Additionally, the lack of adequate resources and services makes it difficult for rural school districts to build and maintain ongoing collaborative relationships with parents (Hammond & Ingalls, 1999;Hammond et al, 1995;Ingalls & Hammond, 1996;Ingalls, Hammond, Dupoux, E., & Baeza, 2006). Additionally, these authors noted rural key professional stakeholders, such as school psychologists, speech and language pathologists and other related service providers, were often times assigned to schools that were not close in proximity, thus making collaboration with team members much more difficult Research has also shown that parental participation in the IEP process has yet to be one of equality and, in many cases, the relationships between parents and educator is, in fact, quite tenuous (Deslandes, Royer, Potvin, & Leclerc, 1999;Friend, 2005;Rock, 2000;Simpson, 1996).…”
Section: Parents As Members Of the Special Education Teammentioning
confidence: 99%
See 1 more Smart Citation
“…A primary reason for less participation is that rural parents have to travel considerably further distances to par ticipate in the special education process. Additionally, the lack of adequate resources and services makes it difficult for rural school districts to build and maintain ongoing collaborative relationships with parents (Hammond & Ingalls, 1999;Hammond et al, 1995;Ingalls & Hammond, 1996;Ingalls, Hammond, Dupoux, E., & Baeza, 2006). Additionally, these authors noted rural key professional stakeholders, such as school psychologists, speech and language pathologists and other related service providers, were often times assigned to schools that were not close in proximity, thus making collaboration with team members much more difficult Research has also shown that parental participation in the IEP process has yet to be one of equality and, in many cases, the relationships between parents and educator is, in fact, quite tenuous (Deslandes, Royer, Potvin, & Leclerc, 1999;Friend, 2005;Rock, 2000;Simpson, 1996).…”
Section: Parents As Members Of the Special Education Teammentioning
confidence: 99%
“…In one rural American Indian community the parents did not approve of the behavior management strategies used by the school professionals. In fact, the parents reported the strategies were not culturally responsive to their home discipline practices (Ingalls, Hammond & Dupoux, 2005;Ingalls, L., Hammond, Dupoux, & Baeza, 2006). Additionally, parents expressed concerns about the unintelligibility of both the special education law and the IEP process.…”
Section: Parents As Equal Informed Decision Makersmentioning
confidence: 99%
“…Second, it would be important to consider various methods of communication (e.g., video calls, text messages, or face-to-face meetings) to allow parents to build trusting relationships. This was of particular interest as establishing connections and building trust has been reported as a challenge for parents and schools in rural settings (Ingalls et al, 2006; Trussell et al, 2008). Participants extended upon this idea further to convey a phone-based approach would likely help reduce stigma and promote engagement by parents.…”
Section: Discussionmentioning
confidence: 99%
“…Working with families of children with disabilities is another challenge facing many rural schools. Compared with schools in urban and suburban areas, special educators in rural schools communicate less often with parents (Jung & Bradley, 2006), and limited access to resources or services impedes the schools’ ability to maintain collaborative relationships with parents (Ingalls, Hammond, Dupoux, & Baeza, 2006; Trussell, Hammond, & Ingalls, 2008). Yet teachers report wanting more training on working with families (Berry et al, 2011), and families want to be more involved with school (Blitz, Kida, Gresham, & Bronstein, 2013).…”
mentioning
confidence: 99%
“…For example, when compared with schools in urban and suburban areas, special educators in rural schools reported communicating less often with parents (Jung & Bradley, 2006). Furthermore, limited access to resources may limit the schools’ ability to foster and maintain collaborative relationships with parents (Ingalls, Hammond, Dupoux, & Baeza, 2006; Trussell, Hammond, & Ingalls, 2008). However, families report a desire to be more involved with schools, and teachers report that they would like more training on how to work with families (Berry et al, 2011; Blitz, Kida, Gresham, & Bronstein, 2013).…”
Section: Challenges Faced By Rural Schools In Supporting Students Witmentioning
confidence: 99%